Meaningful Review of Existing Trends, Expansion, and Future Directions of Green Bond Research: a Bibliometric Approach - Riaz, Tabassum; Selamat, Aslam Izah; Nor, Normaziah Mohd; Hassan , Ahmad Fahmi Sheikh (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
Green bonds serve as an imperative financial tool for mitigating climate change risk and environmental sustainability. It has received significant attention in the current literature, with increased worldwide efforts to fight against global climate change. Yet, the direction of green bonds’ literature is currently unclear. Therefore, this paper aims to deliver a comprehensive vision of the literary landscape of green bond research, in consideration of policymakers, major market players, and investors. To achieve this, bibliometric analysis is performed on 342 filtered articles found in the Scopus database, through VOSviewer and Biblioshiny package. A detailed and descriptive evaluation of scholarly data demonstrates the significance of green bonds in accomplishing the objective of sustainable finance and mitigation of climate change. This study broadens our understanding of the literature and conceptual growth of scholarly discussion of green bonds, which gives insight into developing a strong conceptual foundation and future directions for research.